Single Particle Nanoelectrochemistry Reveals the Catalytic Oxygen Evolution Reaction Activity of Co3O4 Nanocubes. Issue 43 (23rd September 2021) - Quast, Thomas; Varhade, Swapnil; Saddeler, Sascha; Chen, Yen‐Ting; Andronescu, Corina; Schulz, Stephan; Schuhmann, Wolfgang
Abstract: Co3 O4 nanocubes are evaluated concerning their intrinsic electrocatalytic activity towards the oxygen evolution reaction (OER) by means of single‐entity electrochemistry. Scanning electrochemical cell microscopy (SECCM) provides data on the electrocatalytic OER activity from several individual measurement areas covering one Co3 O4 nanocube of a comparatively high number of individual particles with sufficient statistical reproducibility. Single‐particle‐on‐nanoelectrode measurements of Co3 O4 nanocubes provide an accelerated stress test at highly alkaline conditions with current densities of up to 5.5 A cm −2, and allows to derive TOF values of up to 2.8×10 4 s −1 at 1.92 V vs. RHE for surface Co atoms of a single cubic nanoparticle. Obtaining such high current densities combined with identical‐location transmission electron microscopy allows monitoring the formation of an oxy(hydroxide) surface layer during electrocatalysis. Combining two independent single‐entity electrochemistry techniques provides the basis for elucidating structure–activity relations of single electrocatalyst nanoparticles with well‐defined surface structure. Abstract : SECCM and the single‐particle‐at‐the‐tip approach are allied to gain insight into the activity of individual Co3 O4 nanocube particles towards the oxygen evolution reaction. The single‐particle‐at‐the‐tip approach offers the ability to perform accelerated stress tests combined with HR‐TEM to observe structural changes of the nanoparticle during electrocatalysis at high current densities.